Effectiveness of Calcium Hydroxide Against Enterococcus Faecalis Biofilm in Dental Root Canals - haifa nawari, bilqis; Malinda, Yuti; Prisinda, Diani (International Journal Labs, 2025)
Enterococcus faecalis (E. faecalis) is the most widely detected species associated with persistent endodontic infections because it has the ability to form biofilms. This study aimed to identify the effectiveness of calcium hydroxide paste Calcigel® (Prevest DenPro, India) on E. faecalis (ATCC 29212) biofilms in root canals with exposure times of 14, 21, and 28 days. The type of research used was true experimental in vitro by randomly selecting samples of tooth roots on the 14th day of biofilm development and dividing them into six groups: use of Ca(OH)2 as intra-canal medicament for 14, 21, and 28 days, as well as positive control without treatment for 14, 21, and 28 days. Dentin chip suspensions were used for colony form ng units counting to estimates remaining E. faecalis counts. The effectiveness calculation obtained by comparing the test group with the control group at the same treatment duration, with the results of using Ca(OH)2 for 14 days showing a decrease in the number of E. faecalis 96.46%, the results of using Ca(OH)2 for 21 days was 95.20%, while the results of using Ca(OH)2 for 28 days was 94.59%. The results of testing the hypothesis with the ANOVA test showed that there was no significant difference between the effectiveness of calcium hydroxide with exposure to 14 days, 21 days, and 28 days with a significance value of <0.452.